Accelerated Apoptosis of Neutrophils in Familial Mediterranean Fever - Manukyan, Gayane; Aminov, Rustam; Hakobyan, Gagik; Davtyan, Tigran (Frontiers in Immunology, 2015)
The causative mutations for familial Mediterranean fever (FMF) are located in the MEFV gene, which encodes pyrin. Pyrin modulates the susceptibility to apoptosis via its PYD domain but how the mutated versions of pyrin affect apoptotic processes is poorly understood. Spontaneous and induced rates of systemic neutrophil apoptosis as well as the levels of proteins involved in apoptosis were investigated ex vivo in patients with FMF using flow cytometry and RT-qPCR. The freshly collected neutrophils from the patients in FMF remission displayed a significantly larger number of cells spontaneously entering apoptosis compared to control (6.27% ± 2.14% vs. 1.69% ± 0.18%). This elevated ratio was retained after 24h incubation of neutrophils in the growth medium (32.4% ± 7.41% vs. 7.65% ± 1.32%). Correspondingly, the mRNA level for caspase-3 was also significantly increased under these conditions. In response to the inducing agents the neutrophils from FMF patients also displayed significantly elevated apoptotic rates compared to control. The elevated rates, however, can be largely explained by the higher basal ratio of apoptotic cells in the former group. Monitoring of several proteins involved in apoptosis has not revealed any conventional mechanisms contributing to the enhanced apoptotic rate of neutrophils in FMF. Although the exact molecular mechanisms of accelerated neutrophil apoptosis in FMF remain unknown, it may provide a protection against excessive inflammation and tissue damage due to a massive infiltration of neutrophils in the acute period of the disease.